The impact of non-medical switching among ambulatory patients: an updated systematic literature review. Issue 1 (1st January 2019) - Weeda, Erin R.; Nguyen, Elaine; Martin, Silas; Ingham, Michael; Sobieraj, Diana M.; Bookhart, Brahim K.; Coleman, Craig I.
ABSTRACT: Background : Non-medical switching (NMS) is defined as switching to a clinically similar but chemically distinct medication for reasons apart from lack of effectiveness, tolerability or adherence. Objective : To update a prior systematic review evaluating the impact of NMS on outcomes. Data sources : An updated search through 10/1/2018 in Medline and Web of Science was performed. Study selection : We included studies evaluating ≥25 patients and measuring the impact of NMS of drugs on ≥1 endpoint. Data extraction : The direction of association between NMS and endpoints was classified as negative, positive or neutral. Data synthesis : Thirty-eight studies contributed 154 endpoints. The direction of association was negative (n = 48; 31.2%) or neutral (n = 91; 59.1%) more often than it was positive (n = 15; 9.7%). Stratified by endpoint type, NMS was associated with a negative impact on clinical, economic, health-care utilization and medication-taking behavior in 26.9%, 41.7%, 30.3% and 75.0% of cases; with a positive effect seen in 3.0% (resource utilization) to 14.0% (clinical) of endpoints. Of the 92 endpoints from studies performed by the entity dictating the NMS, 88.0%were neutral or positive; whereas, only 40.3%of endpoints from studies conducted separately from the interested entity were neutral or positive. Conclusions : NMS was commonly associated with negative or neutral endpoints and was seldom associated with positive ones.